PERAN KANTOR URUSAN AGAMA DALAM PENANGANAN ALIRAN SEMPALAN: STUDI KASUS KUA KECAMATAN TANJUNG BATU - Jaya, Agus (Direktorat Jenderal Bimbingan Masyarakat Islam, 2015)
Abstract The emergence of White Chicken recitation sect in the district of Tanjung Batu Ogan Ilir of South Sumatra Province, Indonesia caused unrest in society. In a study obtained a description that the factors causing the spread of these sect are the lack of understanding of the true Islamic teaching, a false understanding of the religion concept and economic factors and the society phenomenon that easy to trust to instant promise. To tackle the spread of the sect, the Religious Affairs Office (KUA) of Tanjung Batu district makes three approaches include preventive approach, criminal law approach and the rehabilitative approach. With the commitment of